Influence of Habit on Learning Value of ManageBac Usage in Singapore School Kelapa Gading - Dwirana, Adinda Bilqisth; Nugraha, Jaka (Universitas Negeri Surabaya, 2023)
This study aims to analyze the influence of habit on the learning value of ManageBac usage in a Singapore School Kelapa Gading located in North Jakarta, Indonesia. ManageBac is one of the Learning Management System used by international schools using IB curriculum. The study will apply the UTAUT2 model, which is a theoretical framework used to understand the factors that influence the adoption and use of technology in various contexts. The study will extend the UTAUT2 framework by integrating the habit construct and provide fresh insight into predictors of students' intentions toward ManageBac usage. The study will collect data through a survey questionnaire consisting of 11 questions using Likert scale. The data will be analyzed using Variance-Based Structural Equation Modeling (VB-SEM) using GSCA Pro application. The population of the study will be a total of 112 high school students at Singapore School Kelapa Gading using the saturation sampling technique which includes the population as the sample. The result shows that HT has a significant influence on LV, and the more habitual a user is in using ManageBac, the higher their perceived value of the system. This research will provide insights to teachers that it is important to form a habit for students to use ManageBac and recommendations for future research to use LV instead of PV variable to better understand the context of m-learning.